ANALISIS KELAYAKAN FINANSIAL DAN STRATEGI PENGEMBANGAN USAHA INDUSTRI RUMAHAN GULA SEMUT (PALM SUGAR) DARI NIRA NIPAH DI KELURAHAN PALLANTIKANG - Irmawati Irmawati; Husain Syam; Jamaluddin P Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2015)
This research is aim to know a work-development based on the supplying of nira nipah (sap of nipa palm) as a basic ingredient, production, labor, marketing, financial-feasibility, and work-development strategy. The subject of the study were 30 sap-incisor farmers and a palm sugar home industry in Pallantikang village. The feasibility analysis used were Benefit Cost Ration (BCR), Net Present Value (NPV), Internal Rate of Return (IRR), Break Event Point (BEP), and PBP (Pay Back Period) to know the feasibility of the work. SWOT matrices was used to build work-development strategy of the palm sugar home industry. The result of the study showed that the work-development strategy of a basic ingredient, production, labor, and marketing are suitably done in the research location. The financial-feasibility toward palm sugar home industry in Pallantikang village for the BCR, IRR, BEP (Unit), BEP (Rupiah), and PBP criterion is suitably done. Moreover, based on SWOT analysis, it is found a recommendation for this research that are increasing the operating income; work in cooperation with government to get a capital aid, tools, even training for the owner and the labors of palm sugar, and give a development and training for sap-incisors in order to not making ballo or fermented palm wine